Four-level hysteresis-based dtc for torque capability improvement of ipmsm fed by three-level npc inverter - Saleh Hakami, Samer; Lee, Kyo Beum (Electronics (Switzerland), 2020)
Direct torque control (DTC) is considered one of the simplest and fastest control strategies used in motor drives. However, it produces large torque and flux ripples. Replacing the conventional two-level hysteresis torque controller (HTC) with a four-level HTC for a three-level neutral-point clamped (NPC) inverter can reduce the torque and flux ripples in interior permanent magnet synchronous motor (IPMSM) drives. However, the torque will not be controlled properly within the upper HTC bands when driving the IPMSM in the medium and high-speed regions. This problem causes the stator current to drop, resulting in poor torque control. To resolve this problem, a simple algorithm based on a torque error average calculation is proposed. Firstly, the proposed algorithm reads the information of the calculated torque and the corresponding torque reference to calculate the torque error. Secondly, the average value of torque error is calculated instantaneously as the reference torque changes. Finally, the average value of the torque error is used to indicate the operation of the proposed algorithm without the need for motor speed information. By using the proposed algorithm, the torque can be controlled well in all speed regions, and thus, a better stator current waveform can be obtained. Simulation and experimental results validate the effectiveness of the proposed method.
Keywords: Direct torque control; Hysteresis torque controller; IPMSM; Three-level neutral-pointclamped Inverter